KOMUNIKASI KELOMPOK PELAKU USAHA DALAM PEMBERDAYAAN EKONOMI MASYARAKAT PADA OBJEK WISATA DI KAWASAN PESISIR (STUDI PADA OBJEK WISATA TAMENDAO BEACH) - PAKAYA, SITI MAYASARI; PUTRI, CITRA F.I.L DANO; MURSALIM, MUHAMMAD AKRAM; ANANDA, DEA YULIA R. (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to analyze the communication governance of business actors in community economic empowerment in tourist attractions in coastal areas at Tamendao Beach tourist attraction. This study took data using purposive sampling technique then got 7 informants consisting of 6 business owners and 1 business manager at Tamendao Beach tourist attraction. The results showed that most informants said that in managing Tamendao Beach, the local community almost never experienced disputes. Instead, they work hand in hand in creating a comfortable atmosphere at Tamendao Beach.